Fetal Cartilage-Derived Cells Have Stem Cell Properties and Are a Highly Potent Cell Source for Cartilage Regeneration. Issue 3 (March 2016) - Choi, Woo Hee; Kim, Hwal Ran; Lee, Su Jeong; Jeong, Nayoung; Park, So Ra; Choi, Byung Hyune; Min, Byoung-Hyun
Current strategies for cartilage cell therapy are mostly based on the use of autologous chondrocytes or mesenchymal stem cells (MSCs). However, these cells have limitations of a small number of cells available and of low chondrogenic ability, respectively. Many studies now suggest that fetal stem cells are more plastic than adult stem cells and can therefore more efficiently differentiate into target tissues. However, the characteristics and the potential of progenitor cells from fetal tissue remain poorly defined. In this study, we examined cells from human fetal cartilage at 12 weeks after gestation in comparison with bone marrow-derived MSCs or cartilage chondrocytes from young donors (8–25 years old). The fetal cartilage-derived progenitor cells (FCPCs) showed higher yields by approximately 24 times than that of chondrocytes from young cartilage. The morphology of the FCPCs was polygonal at passage 0, being similar to that of the young chondrocytes, but it changed later at passage 5, assuming a fibroblastic shape more akin to that of MSCs. As the passages advanced, the FCPCs showed a much greater proliferation ability than the young chondrocytes and MSCs, with the doubling times ranging from 2 4 days until passage 15. The surface marker profile of the FCPCs at passage 2 was quite similar to that of the MSCs, showing high expressions of CD29, CD90, CD105, and Stro-1. When compared to the young chondrocytes, the FCPCs showed much less staining of SA-β-gal, a senescence indicator, at passage 10 and no decrease in SOX9 expression until passage 5. They also showed a much greater chondrogenic potential than the young chondrocytes and the MSCs in a three-dimensional pellet culture in vitro and in polyglycolic acid (PGA) scaffolds in vivo. In addition, they could differentiate into adipogenic and osteogenic lineages as efficiently as MSCs in vitro. These results suggest that FCPCs have stem cell properties to some extent and that they are more active in terms of proliferation and chondrogenic differentiation than young chondrocytes or MSCs.